The Usborne book of art ideas - Watt, Fiona (Usborne London, 2009)
Uses a variety of materials to create drawings, paintings, prints and collages. This book features step-by-step instructions for using the ideas to create pictures of their own. It includes lots of ideas for framing pictures and making cards